The business case for design for Six Sigma - Perry, Randy C. (Randy Clair), 1956- (Prentice Hall, 2006)
Successful development and commercialization of new products are critical to the long term viability of any business. The primary goal of product development is to enable a company to meet its goals for profitability and growth by introducing new, improved and innovative products to the market. The failure of a company to commercialize valuable new product ideas results in the commoditization of that company's product portfolio and potential failure of the business itself. In this short cut we examine the business reasons that lead a company to adopt and implement the Design for Six Sigma methodology. During our discussion we examine the product life cycle that all products undergo, beginning with product development and ending with product decline. The impact of new, disruptive technologies on current products is also examined and illustrated with a case study example involving the replacement of vacuum tube technology by the transistor. In addition, an examination of the economics of new product introduction is presented, describing the impact of low priced substitute and "surpriser and delighter" products on existing markets. Using traditional supply/demand economic analysis in combination with the Kano model, the authors explain the dynamic forces which move existing products from premium pricing to a state of commoditization. Finally, the authors take a detailed look at the financial metrics used to measure success in a DFSS project. During this portion of the chapter the authors discuss financial metrics such as Net Present Value; key reasons for failed commercialization programs; and the use of financial sensitivity analysis, including Monte Carlo simulation techniques. This short cut describes in detail how DFSS brings value to companies. Using the language of business, the authors outline how Design for Six Sigma helps companies identify the needs of customers and emerging product trends through the use of a well defined, structured process. The authors also provides the reader with an understanding of how DFSS can be used to counter the forces of product commoditization and the entry of potentially disruptive technologies in the markets served by the business today. Contents What This Short Cut Covers 3 Introduction 4 The Product Life Cycle 4 Where Have All the Vacuum Tubes Gone? 5 Understanding Dynamic Markets: The Kano Model 8 The Role of DFSS 12 Six Sigma Financial Metrics 14 Candy Wrapper Film: A DFSS Case Study 15 How to Measure ...